The Play Experiences of Preschool Children from a Low‐socio‐economic Rural Community in Worcester, South Africa. (8th September 2015) - Bartie, Michelle; Dunnell, Alex; Kaplan, Jesse; Oosthuizen, Dianka; Smit, Danielle; van Dyk, Anchen; Cloete, Lizahn; Duvenage, Mia
Abstract: Occupational therapists believe that play is a child's main occupation and is considered essential for healthy motor, cognitive and emotional development. However, play spaces and activities in low socio‐economic areas are often different to those provided in structured occupational therapy treatment environments. The main objective was to determine play opportunities, activities, equipment, toys and the play environment for 5‐ to 6‐year‐olds living in a low‐socio‐economic community outside a small town in South Africa, in order to understand the nature of play in this environment better. Participant observation together with an adapted photovoice method to capture the play experience was used. Data was analysed using inductive content analysis. Two global themes emerged from the results: "neighbourhood children find ways to play" and "context influences play". Children were given ample opportunity to play and participated in extensive outdoor play. Their games were highly social and involved the imaginative use of found items as toys. Play was also used to make sense of social hazards. An understanding of play in a low‐income context has implications for the development of future play assessments and the provision of play therapy in these communities. Copyright © 2015 John Wiley & Sons, Ltd.